Obstructing the view of the sea - Mumbai Archive Project Team (Jio Institute, 2024)
Yashoda Nakhva, seventy years old, spent most of her life in this house. Recently, she moved to a new place, just a short distance away. Yashoda laments how the dockyard has obstructed the view of the sea from the balcony of the Nakhva house and blocked the cool sea breeze.